Anticoagulant prophylaxis and therapy in children: current challenges and emerging issues. (24th January 2018) - Newall, F.; Branchford, B.; Male, C.
Abstract : Summary: This review is aimed at describing the unique challenges of anticoagulant prophylaxis and treatment in children, and highlighting areas for research for improving clinical outcomes of children with thromboembolic disease. The evidence presented demonstrates the challenges of advancing the evidence base informing optimal management of thromboembolic disease in children. Recent observational studies have identified risk factors for venous thromboembolism in children, but there are few interventional studies assessing the benefit–risk balance of using thromboprophylaxis in risk‐stratified clinical subgroups. A risk level‐based framework is proposed for administering mechanical and pharmacological thromboprophylaxis. More research is required to refine the assignment of risk levels. The anticoagulants currently used predominantly in children are unfractionated heparin, low molecular weight heparin, and vitamin K antagonists. There is a paucity of robust evidence on the age‐specific pharmacology of these agents, and their efficacy and safety for prevention and treatment of thrombosis in children. The available literature is heterogeneous, reflecting age‐specific differences, and the various clinical settings for anticoagulation in children. Monitoring assays and target ranges are not well established. Nevertheless, weight‐based dosing appears to achieve acceptable outcomes in most indications. Given the limitations of the classical anticoagulants for children, there is great interest in the direct oral anticoagulants (DOACs), whose properties appear to be particularly suitable for children. All DOACs currently approved for adults have Pediatric Investigation Plans ongoing or planned. These are generating age‐specific formulations and systematic dosing information. The ongoing pediatric studies still have to establish whether DOACs have a positive benefit–risk balance in the various pediatric indications and age groups.